2003
DOI: 10.1001/archpsyc.60.11.1145
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Affective Responses by Anterior Cingulate and Limbic µ-Opioid Neurotransmission

Abstract: These data demonstrate dynamic changes in mu-opioid neurotransmission in response to an experimentally induced negative affective state. The direction and localization of these responses confirms the role of the mu-opioid receptor system in the physiological regulation of affective experiences in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
281
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 363 publications
(310 citation statements)
references
References 76 publications
24
281
2
3
Order By: Relevance
“…In this sense, it has been recently shown that stress, related to certain suicidal behaviors, induces increases in m-opioid receptor mRNA expression in the rat brain (Yamamoto et al, 2003). In addition, positron emission tomography studies in humans demonstrate the in vivo involvement of these receptors in mood and behavior, further suggesting their potential implication in suicide behaviors (Zubieta et al, 2003).…”
Section: Altered Expression Of L-opioid Receptors In the Brains Of Sumentioning
confidence: 99%
“…In this sense, it has been recently shown that stress, related to certain suicidal behaviors, induces increases in m-opioid receptor mRNA expression in the rat brain (Yamamoto et al, 2003). In addition, positron emission tomography studies in humans demonstrate the in vivo involvement of these receptors in mood and behavior, further suggesting their potential implication in suicide behaviors (Zubieta et al, 2003).…”
Section: Altered Expression Of L-opioid Receptors In the Brains Of Sumentioning
confidence: 99%
“…In particular, opioid release in cortical regions involved in emotional processing appears to suppress the emotive element of pain (Zubieta et al, 2001) and affective states such as sadness (Zubieta et al, 2003), whereas blocking µ-opioid receptors with naloxone increases activity in these regions (Borras et al, 2004). Thus, activation of the endogenous opioid system during psychological stress could suppress the affective and sensory components of pain independently.…”
Section: Introductionmentioning
confidence: 99%
“…This basic set of theoretical notions finds strong validation in the fact that opioids modulate pain and reward satiety (two very ancient homeostatic operations, presumably preceding the classic emotional primes in evolution), while in more complex and extended mammalian brains, opioids also modulate social bonding, play and separation distress (all critical emotional operations of a highly social brain). Both play and quieter forms of social comfort are high opioidergic states, while separation distress is organized in good part by the inverse condition of low opioidergic signals (validated in humans by Zubieta et al, 2003), coupled perhaps with high CRF signals. In this sense, separation distress might reflect an evolutionary extension of pain, while social comfort in a secure attachment perhaps is an evolutionary extension of a basic homeostatic wellness and satiety.…”
Section: On a Fundamental Intrinsic Relationship Between Consciousnementioning
confidence: 99%